Room temperature growth and field emission characteristics of CuO nanostructures. (May 2017) - Kaur, Gurjinder; Saini, Krishna; Tripathi, Amit Kumar; Jain, Vaibhav; Deva, Dinesh; Lahiri, Indranil
Abstract: A variety of CuO nanostructures have been synthesized directly on copper foils by room temperature oxidation of copper through wet chemical method. Alkaline condition necessary for the growth process was maintained by the application of NaOH and NH3 precursors. pH of the solution and reaction time were selected as the process variables. Formation of CuO was confirmed by X-ray diffraction pattern analysis. Evolution of morphologies of the phases formed was characterized by field emission scanning electron microscopy, leading to elucidation of the growth mechanism. Different types of CuO nanostructures were observed to be formed at different process parameters, selected for the present study. Field emission characteristics of CuO nanorods and CuO nanoflakes were also investigated. Emission current density of CuO nanorods and CuO nanoflakes were determined to be 0.90 mA/cm 2 and 0.48 mA/cm 2, respectively. Huge difference in the emission current density indicates that field emission properties of CuO nanostructures are strongly affected by their morphology. Highlights: Synthesis of various CuO nanostructures on copper foils at room temperature. The effect of pH of the solution and reaction time on morphology of CuO nanostructures was investigated. Growth mechanism and field emission of CuO nanostructures were discussed.